Electro-thermal-mechanical coupled crystal plasticity modeling of Ni-based superalloy during electrically assisted deformation - Gao, Jia; Li, Hongwei; Sun, Xinxin; Zhang, Xin; Zhan, Mei (International journal of plasticity, 2022)
•An electro-thermal-mechanical coupled model based on crystal plasticity theory.•Targeted effect of electric current on joule heating and dislocation movement.•Decoupled effects of joule heating and nonthermal on activation energy and dislocation evolution. Electrically assisted (EA) formation has attracted much attention in recent years. However, the multiscale deformation mechanism of materials under multifield (electrical, thermal, and mechanical fields) conditions remains unclear. In this study, an electro-thermal-mechanical crystal plasticity model was developed on the basis of the experimental findings of thermal and nonthermal effects of the pulse current in a superalloy during EA deformation. In this model, electrical resistivity was related to the applied current direction and crystallographic defects (e.g., dislocations) to account for the Joule heating effect. Additionally, the effects of electric current on the dislocation slip—in terms of reduction in the activation energy, softening of the slip resistance, and increase in the mobile dislocation evolution rate—were considered to describe the nonthermal effect. The model developed herein demonstrated that the Joule heating effect is locally distributed and is quantitatively related to the deformation, grain orientation, and dislocation density; the current-density threshold, which plays a role in reducing the dislocation density and slip resistance, was also determined. The existence of the stress difference under EA tension was compared with that under thermal loading with the same temperature history and was attributed to two aspects: (a) nonthermal effects, excluding similar thermal effects, and (b) local Joule heating effect. This model provides a method to quantitatively analyze the EA formation process, which will benefit process control.